Thematic Pathways in Islamic Philosophy Research (2000–2025): From Foundational Texts to Contemporary Debates - Judijanto, Loso (West Science Islamic Studies, 2026)
The paper focuses on studying thematic pathways in research on Islamic philosophy over the period between 2000 and 2025 using bibliometric and network visualization techniques. Data were sourced from Elsevier's Scopus and processed using VOSviewer to visualize authorship networks, citation networks and co-occurring keywords. The analysis revealed that there are dominant themes in Islamic philosophy research, which revolve around Islam and philosophy. Authorship network analysis demonstrates that there are clusters and links among scholarly communities with the number of international connections increasing. Citation analysis shows that classical philosophies and interdisciplinary research papers have had a profound impact on Islamic philosophy research. Moreover, the analysis of co-occurring keywords and the overlay analysis illustrate that a thematic shift takes place from foundational and historical questions to applied topics in Islamic economics, law, education and ethics. Indeed, density visualization shows that, although Islamic philosophy remains a dominant theme, emerging themes reflect its diversity and development. Thus, research on Islamic philosophy transforms into an interdisciplinary and internationally-oriented subject that combines classical ideas and modern issues. The study makes contributions to the literature in that it identifies trends and directions in research on Islamic philosophy.